KONSEP AMIL DAN SABILILLAH DALAM SURAT ATTAUBAH AYAT 60 DAN FIQIH SYAFIâ€™IYAH - Mufid, Muhammad Syahril; Saputro, Eko Andy (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2023)
The problems examined in the study are 1) What are the meanings and concepts of amil and sabilillah in the Qur'an and hadith in the books of commentary and fiqh based on the Shafi'iyah school of thought?. In a study, of course, it has the underlying purpose of this paper, namely to find out the meaning and concept of amil and sabilillah in the letter At Taubah verse 60 based on the interpretation of the Qur'an and hadith and books of fiqh based on the Shafi'i school of thought. This research is library research using descriptive methods and tahlily (analytical) methods, namely describing or explaining the interpretations of the commentators related to the concept of Amil and Sabilillah from all aspects contained in the Qur'an and then strengthened by the interpretations of other commentators. . Amil and Sabilillah are important issues in Islam because they greatly affect the validity of zakat, both zakat fitrah and zakat mal. Not only that, Amil and Sabilillah are a policy from Allah and are the perfection of this religion. Therefore, as a Muslim, I must know who is Amil and Sabilillah so that the zakat paid is valid. This study aims to explain the problems of people who regulate zakat based on the orders of the imam or the government as well as those who fight in the cause of Allah voluntarily. Amil is often mistaken for everyone who takes care of zakat even though amil is only someone who is appointed or given permission by the government, and those who are not sent or given permission by the government, think they are included in the zakat asnaf even though this is not the case and if this happens, the zakat assets will be taken. therefore it becomes invalid to the detriment of the muzakki. Along with the changing times without war and not like before, making asnaf sabilillah interpreted to sabilil khoir so that all forms of goodness get a share of zakat, this is a problem that should explain the letter At Taubah verse 60 about asnaf such as faqir, poor, and others show there is a difference in each asnaf. Keywords: Amil, Sabilillah, Interpretation